Age at the Time of Surgery and Maintenance of Head Size in Nonsyndromic Sagittal Craniosynostosis. Issue 5 (May 2016) - Bergquist, Curtis S.; Nauta, Allison C.; Selden, Nathan R.; Kuang, Anna A.
Abstract : Background: Repair of nonsyndromic sagittal craniosynostosis should durably improve intracranial volume and cranial index. The optimal timing of surgery is not known. The authors previously reported reoperation in patients aged younger than 6 months at primary repair. Methods: Patients undergoing primary reconstruction for sagittal craniosynostosis before age 1 year between 2005 and 2013 at Oregon Health & Science University underwent retrospective computed tomographic determination of cranial index and intracranial volume preoperatively and 2 years postoperatively and head circumference measurements until age 6 years. Results: Fifty-six patients undergoing operation before their first birthday were studied in two groups: those younger than 6 months [34 (61 percent)] and those aged 6 months or older at the time of operation. Head circumference percentile increased immediately after surgery but decreased at 1 and 2 years after surgery, significantly more so in patients younger than 6 months ( p < 0.015 at 1 year; p < 0.011 at 2-year follow-up). Mean 2-year postoperative cranial index was significantly increased in both groups ( p < 0.001), which did not differ preoperatively (younger than 6 months, 76.5; 6 months or older, 78.0) or 2 years postoperatively (younger than 6 months, 88.4; 6 months or older, 87.1; p = not significant). Intracranial volume increased in all patients from before surgery to 2 years postoperatively and was higher in the patients aged 6 months or older ( p < 0.001). Conclusion: Cranial reconstruction for nonsyndromic sagittal craniosynostosis improved cranial index equally in all patients but increased head circumference and intracranial volume significantly more in patients who underwent surgical reconstruction at age 6 months or older. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.